Frequency of Underweight and its Risk Factors in Children Aged 6 to 59 Months - Mohsin Ali Memon; Syed Nauman Raza; Syed Muhammad Zulfiqar Hyder Naqvi; Syed Imtiaz Ahmed Jafry (Liaquat National Journal of Primary Care)
Background: Globally, approximately 104 million children suffer from underweight conditions, with a significant majority residing in regions such as sub-Saharan Africa and South Asia. In Pakistan, the issue of underweight prevalence among children under the age of 5 is alarming across all provinces, ranging from 19.2% in Islamabad Capital Territory to 41.3% in Sindh. Objective: To assess the frequency of underweight and identify its associated factors among children aged 6 to 59 months in Nawabshah City, Sindh. Methods: A cross-sectional study was conducted at Baqai Institute of Health Sciences, Karachi from February 2023 to March 2024. The study included a total of 371 children aged 6 to 59 months. Data collection was performed using interviews and weight measurement. Being underweight was defined as children with a weight-for-age z-score of <-2SD, determined by using WHO child growth standards. Statistical analysis was performed using SPSS version 20. Results: The mean age of the children was 24.21±13.14 months, 198 (53.4%) were female whereas only 44 (11.9%) were completely immunized. Moreover, 111 (29.9%) study children were found to be underweight. Multivariable analysis further revealed that female gender, not exclusively breastfeeding a child for six months, weaning at 6 months of age or above, bottle feeding, and not providing meat to a child in any form were significantly associated with the child being underweight. Conclusion: Around thirty percent of the study children were identified as underweight. Moreover, many participant characteristics and practices studied were significantly associated with children being underweight